The role of local communities in the conservation of cultural heritage sites: A case study of Vietnam - Nam, Nguyen Thanh; Thanh, Nguyen Nghi (Journal of Asian Scientific Research, 2024)
This study examines the significant impact of local community engagement on conserving cultural heritage sites, focusing on active participation, cultural preservation, decision-making, and oversight. Utilizing Structural Equation Modeling (SEM) for analysis, it evaluates how community involvement aids in the maintenance and protection of tangible and intangible heritage aspects. Findings reveal substantial improvements in conservation outcomes due to active community participation, highlighting the critical role of local communities in preserving heritage integrity and cultural values. This emphasizes the necessity of grassroots involvement for lasting cultural legacy preservation. Furthermore, the study stresses the importance of incorporating indigenous knowledge and traditions into conservation strategies to ensure culturally relevant and sustainable outcomes. Although based in Vietnam, the implications of this research are global, advocating for inclusive, community-centric conservation practices that emphasize environmental sustainability and cultural significance. This approach signifies a transformative shift towards heritage conservation models that align with local community ethos, offering valuable insights and recommendations for a more integrative and culturally attuned preservation strategy.